Attention on adolescent mental disorders: the long-term effects on labor market outcomes - Yu, Jia (International Journal of Applied Economics, 2019)
According to a presidential task force about national college health in 2005, 14.9% of college students have been diagnosed with depression or anxiety disorders. Almost 75% of them experienced mental health problems during their early childhood or adolescence. Specifically, this paper examines the longitudinal effects of learning disability and attention disorder, and behavior disorder, of children born in 1980 – 1984, on their labor market outcomes as young adults. This study applies data from the National Longitudinal Survey of Youth 1997 (NLSY97), which documents the transition from school to work, and from adolescence to adulthood. By applying a family fixed effects model with Heckman selection procedure and multinomial logistic regression, the research results show that experiencing mental health illness during childhood is associated with a decreased risk of employment, an increased risk of unemployment, and decreased weekly paid working hours. This effect is strong and significant for males, and barely discernible for females. Hence, childhood mental disorder is an important determinant of individual’s labor market outcomes. Targeting the improvement for boys’ mental illness situation might be beneficial for improving their labor market participation.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US - Yu, Jia (Journal of Studies in Social Sciences, 2015)
Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US
Keywords: dept.eco

Comparison of Single-Payer and Non Single-Payer Health Care Systems: A Study of Health Administration Efficiency - Yu, Jia; Zhang, Yi (Modern Economy, 2017)
The United States spends nearly twice as much per capita on health care as several OECD countries. Based on previous research, universal health care decreases the total health care expenditure due to the single-payer system; it is still unknown whether a mixed health care system has superiority. In this study, we compare and evaluate both quality of care and administrative costs among six developed countries, upon three groups: single-payer universal health care system (Australia and Canada), two-tier health care system (France and Japan), and insurance mandate health care system (Switzerland and the US). The results show that both single-payer system and two-tier system are superior to insurance mandate system on health insurance administration costs. Also, regarding insurance mandate system, the healthcare system in Switzerland is more efficient than that in the US. So, we conclude that it is possible for the US to choose a diverse healthcare system, instead of focusing on one system, to trim the healthcare administration cost and improve the quality of care for the entire country.
2 citations (Crossref) [2023-10-31]
Keywords: dept.eco